2019
DOI: 10.1108/itp-09-2016-0202
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge sharing by entrepreneurs in a virtual community of practice (VCoP)

Abstract: Purpose The purpose of this paper is to examine how entrepreneurs engage in a virtual community of practice (VCoP) to share knowledge. Intensity of engagement is taken as a proxy to measure the strength of knowledge sharing. Design/methodology/approach The archival data spanning over a three-year period from “Start-up-Nation©” (a VCoP purposefully setup for entrepreneurs) are used for analysis. A set of indices are introduced to measure participants’ intensity of engagement in terms of message length, messag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 60 publications
2
35
2
2
Order By: Relevance
“…These hypotheses were not supported, proving that in the analyzed case the availability of knowledge and the perception of this knowledge as generated by a reliable source, are not sufficient to determine either its incorporation in scientific products or learning of new competences. This is in contrast with the findings of other studies in related fields, like virtual communities of professionals [52] or entrepreneurs [86]. This might be due to the specific nature of the community considered: scientific researchers.…”
Section: Structural Model Path Analysis Hypotheses Testing and Fullcontrasting
confidence: 95%
“…These hypotheses were not supported, proving that in the analyzed case the availability of knowledge and the perception of this knowledge as generated by a reliable source, are not sufficient to determine either its incorporation in scientific products or learning of new competences. This is in contrast with the findings of other studies in related fields, like virtual communities of professionals [52] or entrepreneurs [86]. This might be due to the specific nature of the community considered: scientific researchers.…”
Section: Structural Model Path Analysis Hypotheses Testing and Fullcontrasting
confidence: 95%
“…This study builds on the existing body of research that has looked at the positive role of CoPs in social learning and knowledge networks (McLoughlin, Patel, O'Callaghan, & Reeves, 2018;Tseng & Kuo, 2014), driving innovative thinking (Stone et al, 2017) and assisting in professional development (P. Brown, 2015;Khalid & Strange, 2016) in both educational (deChambeau, 2017) and industrial settings (Hafeez, Alghatas, Foroudi, Nguyen, & Gupta, 2019;Huang & Perng, 2017;Pattinson & Preece, 2014).…”
Section: Communities Of Practicementioning
confidence: 99%
“…Technology-supported communities. Wenger's framework (Wenger et al, 2009) for virtual Communities of Practice (VCoPs) (Hafeez et al, 2019) asserts that technology comprises four components: tools, features, platforms and configurations: a) tools: software for specific purposes (i.e. an email client) (Cherry & Latulipe, 2014); b) platforms: packages that combine tools (Spagnoletti, Resca, & Lee, 2015) like for instance Google's G Suite ("G Suite: Collaboration & Productivity Apps for Business," n.d.), used for communication, productivity and storage, with common access and functionality; c) features: specific properties supported by the user interface (i.e.…”
Section: Communities Of Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there have been exploratory studies which surveyed how individuals used the virtual community of practice. Hafeez, Alghatas, Foroudi, Nguyen and Gupta (2018), for example, examined how entrepreneurs engaged in a virtual community of practice to share their knowledge. They observed that entrepreneurs used short and medium messages to contribute to the discussions in the virtual community of practice.…”
Section: Introductionmentioning
confidence: 99%